2012
DOI: 10.1111/j.1755-3768.2012.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a fibrin adhesive for conjunctival closure in trabeculectomy

Abstract: ABSTRACT.Purpose: To assess the safety and efficacy of a fibrin tissue adhesive (Tissucol Duo Ò ) used to close the conjunctiva in trabeculectomy. Methods: A nonrandomized prospective study including 57 patients with chronic simple glaucoma who underwent trabeculectomy surgery. All the trabeculectomies were conducted by the same surgeon using the same surgical technique with the exception that conjunctival closure was achieved by either running Nylon 10 ⁄ 0 suture (n = 29) or using the fibrin glue (n = 28). Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…These include sealing scleral patch grafts or fistula at the time of drainage tube placement for glaucoma [136, 137], placement of conjunctival-limbal autografts for pterygium treatment in children [138, 139] or for limbal stem cell deficiency [140], and conjunctival closure during trabeculectomy [141] or repair of fat prolapse [142]. One of these studies [141] was a nonrandomized prospective trial finding significant reductions in operative time (37.3 ± 4.4 min versus 34.0 ± 4.2, P < 0.006) as well as assessed pain at week 1 (4.7 ± 1.4 versus 3.5 ± 1.3, P = 0.002) and week 2 (2.6 ± 0.9 versus 1.5 ± 0.6, P < 0.001) using fibrin sealant. Two dehiscences occurred in the sealant group ( n = 28) and none occurred in the sutured group ( n = 29).…”
Section: Most Frequent Fibrin Sealant Clinical Literature Applicatmentioning
confidence: 99%
“…These include sealing scleral patch grafts or fistula at the time of drainage tube placement for glaucoma [136, 137], placement of conjunctival-limbal autografts for pterygium treatment in children [138, 139] or for limbal stem cell deficiency [140], and conjunctival closure during trabeculectomy [141] or repair of fat prolapse [142]. One of these studies [141] was a nonrandomized prospective trial finding significant reductions in operative time (37.3 ± 4.4 min versus 34.0 ± 4.2, P < 0.006) as well as assessed pain at week 1 (4.7 ± 1.4 versus 3.5 ± 1.3, P = 0.002) and week 2 (2.6 ± 0.9 versus 1.5 ± 0.6, P < 0.001) using fibrin sealant. Two dehiscences occurred in the sealant group ( n = 28) and none occurred in the sutured group ( n = 29).…”
Section: Most Frequent Fibrin Sealant Clinical Literature Applicatmentioning
confidence: 99%
“…However, similar previous studies involving orbital wall fracture surgery were not found. [3][4][5][6][7][8] In this study, 6-0 polyglactin sutures were compared with a commercial fibrin sealant for the closure of transconjunctival incisions during orbital fracture surgery. The main finding of this study was that the use of fibrin sealant significantly shortened the operative time.…”
Section: Discussionmentioning
confidence: 99%
“…3 Many previous studies have identified a high biocompatibility and shortened operative time with fibrin sealant, but fewer reports have objectively compared fibrin sealant and sutures for conjunctival wound closure, especially during orbital wall fracture surgeries. [3][4][5][6][7][8] The purpose of this study was to compare the efficacy and tolerance of fibrin sealant and sutures for closure of the transconjunctival incision in orbital wall fracture surgery.…”
mentioning
confidence: 99%
“…Freeman et al, compared fibrin glue to sutures in pediatric GDI surgeries for securing the tube to the sclera, the pericardial patch graft over the tube, and closing the conjunctiva and found no differences in complication rates or post-operative IOPs [7]. Martinez-de-la-Casa et al, compared the use of fibrin glue vs 10-O nylon sutures for conjunctival closure in trabeculectomy surgeries and found that each modality was equal in terms if IOP lowering and the use of fibrin glue shortened surgery times and was associated with decreased patient discomfort, though, there were a higher incidence of wound dehiscence in the fibrin glue group [8].…”
Section: Discussionmentioning
confidence: 99%